2017
DOI: 10.1021/acs.est.7b01122
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Flame Retardants in Pregnant Women and Their Transfer to Chorionic Villi

Abstract: The potential for prenatal exposure has recently raised concerns over the health risks of endocrine disruptors; however, knowledge about human prenatal exposure to organophosphorus flame retardants (OPFRs) is lacking. In this study, 2-ethylhexyl diphenyl phosphate (EHDPP), tributyl phosphate (TBP), triphenyl phosphate (TPHP), and tris(2-chloroethyl) phosphate (TCEP) were detected in the majority of chorionic villus samples, with median concentrations of 13.6, 18.8, 11.1, and 0.51 ng/g of dry weight (dw), respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
67
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(71 citation statements)
references
References 44 publications
(90 reference statements)
1
67
3
Order By: Relevance
“…65 Other research demonstrates that exposure to phthalates is associated with molecular changes in placental tissue in sexually dimorphic ways. 66 Though OPEs have been reported in placental tissues 1618 , it remains unclear whether sex specific impacts extend to OPEs or preterm birth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…65 Other research demonstrates that exposure to phthalates is associated with molecular changes in placental tissue in sexually dimorphic ways. 66 Though OPEs have been reported in placental tissues 1618 , it remains unclear whether sex specific impacts extend to OPEs or preterm birth.…”
Section: Discussionmentioning
confidence: 99%
“…12 Data suggest OPEs can be transferred from the mother to her child in utero. 1618 TPHP was detected in placenta samples of dose rats and both TDCIPP and TPHP have been detected in human placenta samples. 17,18 OPEs also have been detected in human chronic villi and deciduae, suggesting transfer early in gestation (i.e.…”
Section: Introductionmentioning
confidence: 98%
“…A number of studies have reported the presence of PEFRs in other human tissues and body fluids. PEFRs were frequently detected in placenta (Ding et al, 2016;Zhao et al, 2017) and breast milk (Sunddkvist et al, 2010;Kim et al, 2014;He et al, 2018a). The median concentration of total PEFRs was around 10-100 ng/g of lipids in breast milk from Sweden and several Asian countries, indicating that substantial exposure occurs at a young age via breastfeeding (Sunddkvist et al, 2010;Kim et al, 2014).…”
Section: Occurrence Of Pefrs In Other Human Samplesmentioning
confidence: 99%
“…Mixtures consisting of 23 xenobiotic chemicals at several humanrelevant levels from already available biomonitoring data were prepared to mimic actual human exposure in the United States (CDC 2018;Frederiksen et al 2010;Högberg et al 2008;Kim et al 2015;Li et al 2015Li et al , 2017Li et al , 2018aNagayama et al 2000;Thomsen et al 2002;Wang et al 2015a;Xiao et al 2011;Zhao et al 2017). The MCF-7 cell was chosen as the experimental model because it is a sensitive hormone-responsive cell line (Levenson and Jordan 1997), and many selected chemicals have been previously reported to be xenoestrogens and EDCs.…”
Section: Experimental Workflowmentioning
confidence: 99%